A multicomponent interconnected composite paper for triple-mode sensors and flexible micro-supercapacitors. Issue 46 (16th November 2020) - Wei, Jing; Teng, Youchao; Meng, Taotao; Bu, Xiangting; Du, Hongbiao; Li, Dagang
Abstract : A multicomponent interconnected composite paper with mechanical robustness, reliable stimulus responsivity and brilliant electrochemical capacitance for human motion/healthcare monitoring. Abstract : A flexible composite paper is designed by imitation of the conch shell structure, comprising graphene (RGO) and a two-dimensional transition metal (Ti3 C2, MXene) as a cuticle layer, and cellulose nanofibrils (CNFs) as the nacre layer. The multi-component interconnected structure provided the RGO/CNFs/Ti3 C2 composite with high conductivity and specific capacitance, as well as stable stimulus-response capability, enabling efficient modulation of interface performance or electronic/ionic transfer under complex environmental stimulations and creating interrelated functioning responses. The RGO/CNFs/MXene composite paper shows an excellent response to pressure, temperature and light. Besides, the fabricated flexible micro-supercapacitor (MSC) exhibits a total volumetric capacitance of 148.25 F cm −3 ( vs. the whole device), excellent cycle stability, and volumetric energy density of 20.5 mW cm −3 . Thus, the composite paper can act as both a multi-sensing unit to pressure/temperature/light and a flexible micro-supercapacitor (MSC) electrode to assemble a mechanically robust integrated device with a reliable stimulus response and moderate electrochemical capacitance to identify users and monitor vital signs by detecting different signal stimuli (motion, pulse, voice and signature), revealing its potential in human motion monitoring, and anti-counterfeiting recognition. This work demonstrates the feasibility of the use of a single functional material to fabricate multi-functional sensors, as well as high-performance supercapacitors, which provides a significant reference for new-generation portable intelligent integrated devices.